India's Space Legislation: The Private Sector Speaks. Issue 2 (1st September 2016) - Venkateshmurthy, Ashok Gubbi; Nagendra, Narayan Prasad
ABSTRACT: India is a long-term investor in building up indigenous space infrastructure and facilities to develop rockets, satellites, and ground systems. However, the space sector is mainly government driven, with private industry participation limited to contributing to the missions executed by the Indian Space Research Organization. With the emergence of the New Space sector, there is a growing private space industry in India that needs to be supported by establishing legal aspects of space activities for private industry activities. This is important at both the international and national level, with the former needing consideration under the purview of the international treaty obligations of India and the latter for the development of the private industry ecosystem. In the present work, we explore some of the fundamental aspects of policies that need to be addressed in the process of forming national space legislation by the government of India. Recommendations in establishing a supportive ecosystem to encourage private space industry activity on a number of important issues are discussed herein.